2020
DOI: 10.1093/cz/zoaa060
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific relationships between urbanization, parasitism, and plumage coloration in house finches

Abstract: Historically, studies of condition-dependent signals in animals have been male-centric, but recent work suggests that female ornaments can also communicate individual quality (e.g., disease state, fecundity). There also has been a surge of interest in how urbanization alters signaling traits, but we know little about if and how cities affect signal expression in female animals. We measured carotenoid-based plumage coloration and coccidian (Isospora spp.) parasite burden in desert and city populations of house … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Song sparrows from suburban habitats exhibited slightly elevated heterophil counts compared to their rural counterparts, though the biological significance of this finding is somewhat unclear. Several previous studies have found birds inhabiting urban environments experience increased risk of infection from avian diseases (e.g., avian malaria, poxvirus, and coccidia) compared to rural dwelling birds (Bichet et al, 2013;Jiménez-Peñuela et al, 2019;Sykes et al, 2021). Consequently, birds inhabiting highdensity urban environments tend to have greater investment in innate immunity (Møller, 2009b;Audet et al, 2016).…”
Section: Effects Of Low-density Urbanization On Immune Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Song sparrows from suburban habitats exhibited slightly elevated heterophil counts compared to their rural counterparts, though the biological significance of this finding is somewhat unclear. Several previous studies have found birds inhabiting urban environments experience increased risk of infection from avian diseases (e.g., avian malaria, poxvirus, and coccidia) compared to rural dwelling birds (Bichet et al, 2013;Jiménez-Peñuela et al, 2019;Sykes et al, 2021). Consequently, birds inhabiting highdensity urban environments tend to have greater investment in innate immunity (Møller, 2009b;Audet et al, 2016).…”
Section: Effects Of Low-density Urbanization On Immune Functionmentioning
confidence: 99%
“…Shifts in energy budgets and higher oxidative stress in urban birds also may be associated with altered immune function (Watson et al, 2017;Cummings et al, 2020a,b). Indeed, urban dwelling birds tend to exhibit infection more often than rural birds, which could cause or be the result of altered immune function (Hamer et al, 2012;Bichet et al, 2013;Giraudeau et al, 2014;Rouffaer et al, 2017;Jiménez-Peñuela et al, 2019;Sykes et al, 2021). Interspecific comparisons among urban and rural dwelling avifauna indicate urban birds cope with increased disease exposure by investing in a more robust immune system (Møller, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…In prior work on these finch populations, researchers have shown that males are consistently more colorful and healthier (including having less coccidiosis) in rural compared to urban areas 22 24 . However, it was recently found that urban female house finches are less severely infected by coccidia than rural females 42 . This opposing pattern between males and females suggests complex disease dynamics in urban areas (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, females can also use plumage colouration as a signal of individual quality (Sykes et al . 2020). However, Sykes et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, Sykes et al . (2020) reported that females of the house finch ( Haemorhous mexicanus ) were less colourful and had a lower parasite load in urban than in rural areas. These authors suggested that urbanisation can disrupt condition‐dependent colour expression.…”
Section: Discussionmentioning
confidence: 99%